TOLERANSI DALAM PERSPEKTIF PIAGAM MADINAH - Erman Erman (Lembaga penelitian dan pengabdian kepada masyrakat, 2011)
This article analyzes about kerukunan lives people get religion in Madinah's Charter. In that Madinah's Charter is managed about relationship among people gets religion, ethnical and islandic different one. A marked diiferences available within fellow being don't be made reasons for mutually diferentiates mutually between they. Mark sense that difference just intent that they ca11 mutually know. Mark sense that diiference just intent that they can all those are equation principle that exist in Madinah's Charter.